Computational methods and points for attention in absolute configuration determination - Zhu, Huajie; Wang, Yufang; Nafie, Laurence A. (Frontiers in Natural Products, 2023)
With the rapid development of high performance computers and computational methods including software, more and more experimental chemists have tried to use computational methods, such as optical rotation ((OR) including the matrix model), optical rotatory dispersion (ORD), electronic circular dichrosim (ECD or CD) and vibrational circular dichroism (VCD), magnetic shielding constants, namely nuclear magnetic resonance (NMR), to explain and/or assign absolute configuration (AC) for various compounds with reports increasing dramatically in the area of natural products. However, every method has its range of application. This leads to incorrect conclusions in some cases for researchers who are not familiar with these methods. In this review, we provide experimental chemists and researchers with more computational details and suitable suggestions, and especially with experience that may be helpful for readers to avoid falling into the pitfalls in computations. Finally, the use of simplified models to replace the original complex structures with a long sidechain is discussed. The fundamental basis for using models to represent complex chiral compounds, such as in OR calculations, is the existence of conformation pairs with near canceling conformer contributions that justify the use models rather than the original compounds. Through examples, we introduce the transition state (TS) calculation in the review. The TS study may provide benefits for readers in this area to use and master for their AC study. This review will summarize the general concepts that are involved in the study of AC determinations.